2021
DOI: 10.1249/mss.0000000000002787
|View full text |Cite
|
Sign up to set email alerts
|

Acute Physical and Mental Activity Influence on Concussion Recovery

Abstract: Introduction: Physical activity (PA) and mental activity (MA) postconcussion has received renewed attention to improve concussion management; however, most protocols start after several days and do not assess the acute window. Therefore, the purpose of this study was to assess PA and MA in the first 48 h postconcussion on the time to symptom-free status and return to play. Methods: We recruited 78 NCAA Division I athletes (male, 51.3%; age, 19.6 ± 1.4 yr; height, 173.7 ± 11.5 cm; weight, 80.1 ± 23.2 kg) who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…1 There is a growing body of evidence that early initiation of PA after concussion decreases recovery time, [8][9][10] and a recent study observed shorter symptom duration with PA initiation within the first 48 hours after concussion. 11 Building on this existing evidence, our results suggest an additional potential benefit of early PA in kinesiophobia reduction for those prone to persistent symptoms after concussion.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…1 There is a growing body of evidence that early initiation of PA after concussion decreases recovery time, [8][9][10] and a recent study observed shorter symptom duration with PA initiation within the first 48 hours after concussion. 11 Building on this existing evidence, our results suggest an additional potential benefit of early PA in kinesiophobia reduction for those prone to persistent symptoms after concussion.…”
Section: Discussionsupporting
confidence: 60%
“…8 Recent research supports initiating physical activity (PA) early in recovery to decrease symptom duration and reduce the risk of developing persistent symptoms. [8][9][10][11] Current concussion consensus guidelines recommend an initial 24-to 48-hour period of rest followed by introduction of aerobic exercise as tolerated even while symptoms are still present. 1 However, there may be barriers to engaging in PA early after concussion, including self-limiting symptoms that reduce the propensity for exercise.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although every effort was made to instruct patients to complete HEPs as prescribed, as is the case with any at-home treatment program, it is not known how often and to what extent each patient completed their rehabilitation, limiting our ability to draw conclusions about a dose-response relationship. Additionally, although both groups were provided the same recommendations regarding aerobic physical exercise, it is possible that the HEP treatment group engaged in more physical activity than the PPT patients, which could have contributed to faster recovery [ 41 , 42 ]. Finally, generalizability is limited by a relatively homogenous sample related to race and ethnicity and due to the analytic sample receiving care within a specialty concussion clinic in a major metropolitan area with onsite access to PT and healthcare professionals trained in the management of SRC.…”
Section: Discussionmentioning
confidence: 99%
“…Current guidelines recommend rest during the “acute phase” (first 24 to 48 h) of concussion recovery, and then gradually increasing activity if symptoms do not worsen. In the February 2022 issue of Medicine & Science in Sports & Exercise ® ( MSSE ), Buckley and colleagues (1) hypothesize that even within the first 48 h after concussion, moderate MA and PA that does not exacerbate symptoms may be beneficial. They conducted a prospective observational study of collegiate athletes who sustained a sports-related concussion (SRC).…”
Section: Acute Physical and Mental Activity Influence On Concussion R...mentioning
confidence: 99%